Nanotechnology and Nanomaterials for Medical Applications - Chin, Bridgid; Juwono, Filbert Hilman; Yong, Kelvin Sheng Chek (2022)
Today, nanotechnology has been of great interest in medical applications. Such technology opens many possibilities in the medical field, such as tissue and implant engineering, and nanomedicine. In particular, nanotechnology brings about nanomaterials for tissue replacement, organ reconstruction, and molecular-level diagnosis and treatment. This chapter aims to give an overview of the use of nanotechnology for medical applications, along with a discussion on the recent developments and challenges. This chapter also includes the exploration of the cores of nanotechnology including the nanomaterials and nanotools with the focus on medical applications. The nanomaterials and designs are discussed along with their advantages. The discussion is supplemented with various applications of the nanoparticles, namely, in the applications of diagnosis, treatment, and tissue and implant engineering. Furthermore, nanobiosensors are also discussed in this chapter. Nanobiosensors are another fascinating application of the nanoparticles where the nanoparticles introduce many benefits of nanomaterials into the application of biosensors. Lastly, future challenges and prospects are explained in detail.